Effect of Burning Stubble and Rice Straw on Concentration of PM2.5 Particulate Matter in Atmosphere : A Case study of Ban Nong Khon Community, Mueang Mai Subdistrict, Ratchasan District, Chachoengsao Province - Prateepchanachai, Sarinya; Jongjun, Yuthanarong; Monmongkol, Tanatat (Burapha Science Journal, 2024)
Background and Objectives : To study the problems and causes associated with the burning of stubble and rice straw in relation to the mass concentration of PM2.5 particulate matter in the atmosphere of Ban Nong Khon community, Muang Mai Subdistrict, Ratchasan District, Chachoengsao Province. The research aimed to compare the PM2.5 concentrations resulting from the burning of stubble and rice straw with the air quality standards set by the Pollution Control Department. Furthermore, it aimed to assess the emission rate of pollutants post-harvest. Methodology : The research utilized research tools, such as process flow diagrams, to collect data on rice cultivation activities and analyzed the relationships between the problems and causes of stubble and rice straw burning using fishbone diagrams. Main Results : Rice farmers lacked knowledge in managing stubble and rice straw. They believed that burning could effectively control weed and pests, and there was a labor shortage. Another contributing factor was the working methods, as farmers needed speed in soil preparation and plowing for the next planting cycle. The study also found that the PM2.5 particulate matter concentration in the atmosphere between May 20 - 26, 2023, exceeded the air quality standards set by the Pollution Control Department for three days. Conclusions : The air quality index measurements indicated a beginning of adverse health impacts on the population. Additionally, the study found that the amount of PM2.5 particulate matter in the atmosphere resulting from the burning of stubble and rice straw left in the rice cultivation area after harvest, with different moisture levels, during the periods of 0, 10, 20, and 30 days, decreased as the burning time increased. The moisture content decreased to 80.8%, 46.8%, 24.5%, and 12.7% (wet basis) respectively. Consequently, the amount of PM2.5 particulate matter in the atmosphere decreased, with concentrations of 35, 30, 24, and 21 μg/m3 respectively. The emission rate of PM2.5 particulate matter was calculated to be 5.4 grams per kilogram of stubble and rice straw.